2022
DOI: 10.3390/f13040560
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Origins of Soil Organic Matter in Different Land-Uses in the Highlands of Ethiopia

Abstract: In the Ethiopian highlands, clearance of Afromontane dry forest and conversion to crop and grazing land lead to land degradation and loss of soil organic matter (SOM). Eucalyptus is often grown on degraded soils, and this results in the partial recovery of soil carbon stocks. The aim of this work was to assess the biological sources of SOM in this land-use sequence. In top-soils (0–10 cm) of four land-use systems, namely remnant natural forest, eucalyptus plantation, cropland, and grazing land, in the Ethiopia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The forest covers c. 68 ha at c. 2500 meters above sea level. The forest is considered an old-growth, seasonally dry-evergreen Afromontane forest growing on slopes of 10-40° ( Assefa et al., 2018 ; Belay et al., 2018 ), and is embedded in a mosaic of (degraded) grass- and croplands ( Assefa et al., 2022 ). The climate of the mountainous study area is seasonally dry subtropical, with warm summers and dry winters (Köppen–Geiger classification ‘Cwb’, Peel et al., 2007 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The forest covers c. 68 ha at c. 2500 meters above sea level. The forest is considered an old-growth, seasonally dry-evergreen Afromontane forest growing on slopes of 10-40° ( Assefa et al., 2018 ; Belay et al., 2018 ), and is embedded in a mosaic of (degraded) grass- and croplands ( Assefa et al., 2022 ). The climate of the mountainous study area is seasonally dry subtropical, with warm summers and dry winters (Köppen–Geiger classification ‘Cwb’, Peel et al., 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the Gelawdiwos forest, at least 41 woody species of 29 families have been recorded, dominantly woody angiosperms ( Wassie et al., 2010 ; Assefa et al., 2022 ). The only woody gymnosperm is Afrocarpus falcatus (syn.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 59.65 Mg C ha ⁻1 was discovered in Minjar Shenkora's parkland agroforestry practice, proving the system's necessity due to the higher density of trees (Tsedeke, Dawud, & Tafere, 2021). Compared to grassland and agriculture, the soil of the natural forest had concentrations of C that were roughly 4.4 and 3.7 times higher, respectively (Assefa et al, 2022). When compared to forest soil, grazing area had the greatest reduction in total soil C storage (0-50 cm), followed by cropland (50%) and eucalyptus plantations (47%) (Ahmed, Assefa, & Godbold, 2022).…”
Section: Carbon Storage Potential and Soil Fertility Enhancementmentioning
confidence: 98%
“…Further, the results showed that the mean soil pH in the 9-year-old E. globulus plantation was 9.25% lower than in grassland. Eucalyptus trees are known to release certain organic acids into the soil through their root systems and fallen leaves [83]. Tese organic acids can contribute to soil acidifcation, potentially lowering the pH of the soil.…”
Section: Te Efect Of Land-use Change On the Chemical Properties Of Th...mentioning
confidence: 99%